IMAGING CHARACTERISTICS AND DETECTION RATE OF COMMON BILE DUCT STONES BY ULTRASOUND AND MAGNETIC RESONANCE CHOLANGIOPANCREATOGRAPHY (MRCP) IN AN ERCP-CONFIRMED COHORT AT VINMEC TIMES CITY INTERNATIONAL HOSPITAL, 2022-2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the imaging characteristics of common bile duct stones on magnetic resonance cholangiopancreatography (MRCP) and compare the detection rates of ultrasonography and MRCP in patients with stones confirmed by endoscopic retrograde cholangiopancreatography (ERCP).Methods: A retrospective study was conducted on 48 patients at Vinmec Times City from 2022 to 2025. All patients underwent ultrasonography, MRCP, and ERCP. As all patients were ERCP-positive, the study assessed detection rates rather than specificity, predictive values, or overall diagnostic accuracy.Results: Ultrasonography detected stones in 27/48 patients (56.3%; 95% CI: 42.3–69.3%), compared with 47/48 (97.9%; 95% CI: 89.1–99.6%) for MRCP, representing a 41.6-percentage-point difference (McNemar test, p
Keywords: Common bile duct stones; Ultrasound; Magnetic resonance cholangiopancreatography; MRCP; ERCP; Detection rate.